The Acceptance of COVID-19 Vaccine: The Projection from the First Year of COVID-19 Pandemic in Indonesia - Rimawati Aulia Insani Sadarang; Tri Addya Karini; Yessy Kurniati (Preventia : The Indonesian Journal of Public Health, 2023)
The Pandemic of COVID-19 affected not only the health sector but also other sectors. Herd immunity through vaccination was recommended by experts. This study purposed to describe the acceptance of the COVID-19 vaccine and to discover predictive factors of COVID-19 vaccine acceptance in Indonesia. This is a cross-sectional study. Data collection used an online platform conducted in August 2020. The questionnaire based on Survey Tool and Guidance by WHO Regional Office for Europe. Logistic regression was run to identify associated factors and to build a predictive model of vaccine acceptance. There were 164 respondents aged 19 – 56 years. About 70.1 percent of respondents showed a willingness to accept the vaccine for COVID-19. The predictive model consisted of age, perceived probability that has been infected and trust in government press releases with performance reaching 73 percent.  The trust of people in the government was the most important key to engaging people in vaccination. Evidence-based messaging delivered regularly by the government and consistent action between the government and health officers would educate and lead people's risk perceived and the decision to be vaccinated.